Pérdida de la patria potestad por violencia intrafamiliar - Aguirre Bermeo, Delia María (2013)
This thesis, whose theme is "loss of parental rights by family violence" consists of six chapters in which relevant aspects of the topic under investigation are described. In the introduction, an analysis of the loss of parental rights as a result of domestic violence is, on the critical targets domestic violence, which increases without finding solutions especially in the case of children, described the general and specific objectives, hypothesis, independent and dependent variables and resources are detailed. The theoretical framework consists of background research, foundation, doctrine, jurisprudence, law and comparative law relating to custody and domestic violence. In the methodology, the methods used are detailed, the techniques applied in the field , with the application of surveys to citizens of Canton La Maná , and the interview data were tabulated, and then formulate report research and testing of the hypothesis. The proposed legal reform increasing a numeral is made to art. 113 of the Code on Children and Adolescents, in order to consider the loss of parental authority by domestic violence, finally conclusions and recommendations are detailed